Legislative control for the sale and supply of pseudoephedrine in community pharmacy in Malaysia / Siti Hufaidah Suhimi, Noraniza Ahmad and Norhasnza Mohamad - Suhimi, Siti Hufaidah; Ahmad, Noraniza; Mohamad, Norhasniza (2011)
Pseudoephedrine is commonly used to treat cold and allergies but at the same time is being misused in illegal manufacture of methamphetamine. Community pharmacy is one of the sources where pseudoephedrine can be obtained as well as diverted. Laws in Malaysia seem insufficient to curtail this problem. Thus, the sale and supply of pseudoephedrine in community pharmacy needs to be fully addressed to prevent the illegal manufacturing of methamphetamine. This study is to examine and compare the current laws in controlling sale and supply of pseudoephedrine in community pharmacy between Malaysia, United States of America and United Kingdom so as to highlight the inadequacies of the laws in Malaysia. Subsequently, it is to recommend the methods in controlling the problem. This study adopted qualitative research methodology where the information gathered from journals, reports, articles, books and semi-structured interview. From this research, it was discovered that the Poisons Act 1952 is insufficient to control the sale and supply of pseudoephedrine in community pharmacy. The penalties imposed under the Poisons Act 1952 should be reviewed as it is deemed to be low and non deterrence. Apart from that, the obvious lacking is the control on the retail sale of pseudoephedrine compared with laws in United States of America and United Kingdom. Moreover, Malaysian Pharmacy Board is not fully utilised to deter the reoccurrence of the offence. Thus, there is a need to improve on the administrative and legislative aspects in regards to the control of sale and supply of pseudoephedrine in community pharmacy in Malaysia.